Design of an impeller for a fire fighting pump. (August 2020) - Paluch, Maciej; Noga, Marcin
Abstract: The article presents the design of a single-stage centrifugal pump impeller for use in a fire vehicle. For such a task, the set utility parameters were determined, and then several methods were used to determine the geometry and dimensions of a given impeller. The project uses A. Stepanoff's formulas, correction of power consumption reduction (Pfleiderer coefficient), as well as the method of point selection of the width of the impeller cross-section in relation to the changing radius of the impeller. A graphical representation of the pump flow rate and pump head depending on the type of impeller and the pump characteristic speed has enabled convenient analysis in terms of assumed pump performance. The procedure adopted in the project did not require the use of advanced engineering tools. The obtained result in the form of geometry and dimensions of the designed result coincides with the parameters of the impellers used in fire pumps currently in use. In the last step of the project, a three-dimensional impeller model was developed, which is a good starting point for optimization by simulation and then experimental verification on a real object.